Coming up roses - Carson, Michael (Great Britian : Black Swan, 1990)
A story set in the fictional country of Ras Al Surra, which is a satire on Arab politics and British bureaucracy. Sultan Nabil, ex-hippy and now bohemian ruler of Zibda, wants to keep the peace but all King Fadl of Ras Al Surra wants is a piece of Nabil's Zibda
Keywords: Adult Book -- Fiction -- Homosexuality